DISTINGUISHING BETWEEN KIDNAPPING AND FORCED UNLAWFUL IMPRISONMENT - Akbaralieva Mukhayyo Karamatullo qizi (Scholar Express Journals, 2025)
At the beginning of the article, the concept of human freedom is revealed, and what types of freedoms exist in jurisprudence. The article distinguishes between two related compounds that infringe on human freedoms: kidnapping and forced unlawful imprisonment. The definition of kidnapping is given. Signs of human abduction are revealed. The signs of forced unlawful imprisonment are revealed. The opinion of various authors on the distinction between kidnapping and forced unlawful imprisonment is given. The article provides a polemic.
Keywords: Human freedom; physical freedom of a person